Human Strategies for Multitasking, Search, and Control Improved via Real-Time Memory Aid for Gaze Location - Taylor, P.; He, Ze; Bilgrien, Noah; Siegelmann, Hava T. (Frontiers in ICT, 2015)
OBJECTIVE: We aimed to elucidate how our domain-general cuing algorithm improved multitasking performance and changed behavioral strategies in human operators. BACKGROUND: Though many gaze-control systems have been designed, previous real-time gaze-aware assistance systems were not both successful and domain general. It is largely unknown what constitutes optimal search efficiency using the eyes, or ideal control using the mouse. It is unclear what the best coordinating strategies are between these two modalities. Our previously developed closed-loop multitasking aid drastically improved multitasking performance, though the behavioral mechanisms through which it acted were unknown. METHODS: We performed in-depth analyses and generated novel eye tracking and mouse movement measures, to explore the complex effects of our helpful system on gaze and motor behavior. RESULTS: Our overlay cuing algorithm improved control efficiency and reduced well-known biases in search patterns. This system also reduced micromanaging behavior, with humans rationally relying more on imperfect automation in experimental assistance cue conditions. We showed that mouse and gaze were more independently specialized in the helpful cuing condition than in control conditions. Specifically, with our aid, the gaze performed more global movement, and the mouse performed more local clustered movement. Further, the gaze shifted towards search over processing with the helpful cuing system. We also illustrated a relationship between the mouse and the gaze, such that in these studies, "the hand was quicker than the eye." CONCLUSIONS: Overall, results suggested that our cuing system improved performance and reduced short term working memory load on humans by delegating it to the computer in real time. Further, it reduced the number of required repeated decisions by an estimate of about one per second. It also enabled the gaze to specialize for improved visual search behavior, and the mouse to specialize for improved control.